Embryonic Markers association in Mice Bearing Mammary Adenocarcinoma (AN3) transplantable tumor model - Alshammari, Ahmed Majeed (Iraqi Journal of Cancer and Medical Genetics, 2015)
AN3 tumor model had special importance as breast cancer model to evaluate new and novel therapeutic agents and there is need to study the tumor associated markers presence during AN3 tumor growth. Most common markers are Carcinoembryonic antigen (CEA) and α-fetoprotein (AFP) which are cells surface glycoproteins. Oncofetal antigens involved in cell adhesion marker for cancers diagnosis and prognosis and normally they are not present in the blood of healthy adults. AN3 is transplantable mammary adenocarcinoma tumor used as in vivo model for years in cancer research for human breast cancer. Hence studying the presence of associated tumor antigens that extensively used as tumor markers (AFP and CEA) is necessary to characterize the model and determine the usefulness to use them as follow up markers after testing therapeutic agents in this model. Healthy and pregnant healthy female mice were used as control groups and AN3 transplanted mice measured after tumor grow to reach at least 0.5 cm. The results showed that CEA is markedly high in mice bearing tumors while no presence of it in both control groups. AFP had a different picture as the higher percentage was in the pregnant females, which is very normal because AFP is a fetal protein, but mice bearing tumor significantly higher concentration than healthy mice. In conclusion, AFP and CEA are useful markers to be used for AN3 model in experimental evaluation of novel therapies follow up